Broad City. [videorecording (DVD)] Season 1 - Glazer, Ilana; Jacobson, Abbi (Paramount, 2014)
Follow the adventures of two best friends working the big city. No matter how bad it gets, and despite their glaring dissimilarities, these "broads" are always down with whatever hits them--sort of.